Formulation of fish feeds with high level of protein - bound methionine and lysine for African catfish (Clarias gariepinus) fingerling's growth - Siti Nurhafa Imra Naqtahnain Hamid (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2017)
This study is focusing on formulating a fish feed with high level of protein-bound methionine and lysine for African catfish fingerlings in a lab scale production. The formulated fish feeds were consisted of several potential feedstuff ingredients. The chosen feedstuff ingredients were earthworm powder, fish meal, soybean wastes, L. leucocephala leaves, and rice bran. Each of the feedstuff ingredients used in the formulation was underwent proximate analysis such as amino acid profile (HPLC analysis), crude protein analysis (Kjehdahl method), crude lipid analysis (Soxtec Extraction method), moisture (Foh method) and ash content (Sluiter method) in order to obtain their nutritional composition. The Design of Experiment (DOE) through Design Expert software was used to formulate the fish feed. Gas Chromatography (GC) analysis was conducted to analyze for methionine and lysine level in the formulated fish feeds. Three formulations of fish feeds obtained from Design Expert software along with commercial fish feed were underwent feeding trials to study the growth rate, feed conversion ratio, survival rate and methionine and lysine digestibility of African catfish fingerlings. The African catfish fingerlings were obtained from local fish farm located in Jitra Kedah, Malaysia.